Estrategias para generar una convivencia armónica frente a situaciones de violencia dentro del núcleo familiar - Muñoz Vargas, Julady Janeth (2021)
This case study on strategies to generate a harmonious coexistence in the face of situations of violence within the family nucleus, the intervention plan in systemic therapy was carried out. A generalized anxiety mental disorder was determined during the evaluation, on the other hand, factors that influence health status and contact with health services were highlighted within the ICD10 classification of mental and behavioral disorders, for To support this diagnosis, psychometric instruments such as: HAMILTON ANXIETY SCALE and INTRAFAMILY VIOLENCE QUESTIONNAIRE were used. In addition, a crisis was found within the diagnosis of family structure, which was, not being able to conceive children on her part, which had an impact on the changes in his behavior towards her, temporarily disadjusting the fulfillment of parental roles.